Insight into the Interaction of Perovskite‐Like Surfaces (LaMnO3 and LaCoO3) with Ar, H2, CO, and O2 through NAP‐XPS Analysis (2024)
ABSTRACT: Perovskite-like oxides present huge chemical variability and a wide range of applications as catalysts for oxidation reactions. The interaction of several small gas molecules with the surface of LaCoO3 and LaMnO3 perovskite-like oxides was studied by Near Ambient Pressure X-ray photoelectron spectroscopy (NAP-XPS) and CO Temperature Programmed Desorption (CO-TPD). Surface chemical changes such as the Osurf/Olattice and cation B oxidation state ratios were analyzed as a function of temperature (400 K, 450 K, 500 K, 550 K, and 650 K) under diferent gas atmospheres like Ar, CO, H2, and O2. It was found that there was a partial surface reduction when H2 and CO were used in the reaction, and therefore, the cation B oxidation state (Mn4+/Mn3+ and Co3+/Co2+) ratio decreased. Under the CO stream, carbonate species were formed, presenting a C1s signal between 284.5 eV and 287 eV. The CO2 evolution during the reaction at temperatures greater than 500 K was associated with CO activation over or near to surface oxygen species. A Mars-van Krevelen mechanism was proposed for the process, fnding signifcant diferences between LaCoO3 and LaMnO3 perovskite-like solid catalysts behavior.